Dual blockade of DPP-4 and CXCL12/CXCR4 axes synergistically protects podocytes in lupus nephritis - Hu, Hui-miao; Li, Yong-chun; Zhang, Yang-ming; Zhu, Teng-yu; Yong, Wei-jing; Gan, Yu-hui; Liu, Chen; Duan, Rui-ying; Xu, Hong-de; Zhao, Zhan-zheng; Qi, Yuan-yuan (Frontiers in Pharmacology, 2026)
BackgroundLupus nephritis (LN), a severe complication of systemic lupus erythematosus (SLE), is characterized by podocyte injury that contributes to disease progression. Dipeptidyl peptidase-4 (DPP-4) inhibitors, though developed for diabetes, have shown renoprotective potential. However, DPP-4 inhibition may elevate CXCL12/CXCR4 signaling, a pathway implicated in LN pathogenesis. This study aimed to determine whether dual DPP-4 and CXCL12/CXCR4 blockade confers enhanced renal protection in LN.MethodsMRL/lpr lupus-prone mice were treated with the DPP-4 inhibitor linagliptin, either alone or in combination with the CXCL12/CXCR4 axis antagonist AMD3100. We evaluated renal function, histopathology, podocyte structure, and markers of oxidative stress, fibrosis, and inflammation. In vitro assays using DPP4-knockout podocytes were also performed to elucidate underlying mechanisms.ResultsDPP4-deficient podocytes exhibited elevated CXCL12/CXCR4 expression and modest nephrin upregulation. Co-treatment with AMD3100 further increased nephrin expression compared to linagliptin alone. In vivo, linagliptin monotherapy reduced proteinuria and serum creatinine but also increased CXCL12/CXCR4 expression. Combined therapy significantly decreased proteinuria, serum creatinine, anti-dsDNA, and ANA titers. Histological analysis showed reduced mesangial proliferation and interstitial inflammation. Transmission electron microscopy and immunostaining demonstrated improved podocyte foot process integrity and upregulation of nephrin and podocin. Dual blockade also reduced renal oxidative stress (DHE, NOX4), fibrosis markers (α-SMA, fibronectin), and inflammatory mediators (NF-κB p65, NLRP3).ConclusionCombined DPP-4 and CXCL12/CXCR4 axis inhibition synergistically enhanced podocyte protection and attenuated renal inflammation, fibrosis, and oxidative stress in lupus nephritis. These findings support dual blockade as a promising therapeutic strategy for LN.